Effect of nanoaquahelate compounds on the activity of blood enzymes in cows with different tone of the autonomic nervous system - Ilchyshyn, M.; Karpovskyi, V.; Zhurenko, O.; Hryshchuk, I.; Karpovskyi, P.; Kryvoruchko, D.; Hryshchuk, A.; Karpovskyi, V.; Todoriuk, V.; Melnychuk, V. (Scientific Progress & Innovations, 2025)
When using feed additives to increase the productivity of cows, it is necessary to take into account the individual characteristics of the organism of these animals. This will ensure greater efficiency of the use of additional feed additives for the dairy herd. The aim of the study was to determine the effect of the nanopreparation on the enzyme levels in the blood of cows with different tone of the autonomic nervous system. For the study, 3 groups of cows were formed according to the tone of the autonomic nervous system using a variation-pulse oximetry study, each of which was then divided into control and experimental groups. The experimental group during lactation for 30 days is fed a nanopreparation of trace elements Mg, Zn, Ge and Fe, at a dose of 10 ml per day with the content (mg/day): Mg – 50 mg/day, Zn – 50 mg/day, Ge – 10 μg/day and Fe – 20 mg/day. According to the results of biochemical studies, it was found that the activity of enzymes in the control group with normotension was 1.64 times higher in aspartate aminotransferase (P<0.01), alanine aminotransferase by 37.7 % (P<0.001), gamma-glutamyltransferase by 1.6 times (P<0.01) compared to the experimental group of animals. In the experimental group with vagotonia, the activity of enzymes was lower in aspartate aminotransferase by 2.33 times (P<0.01), alanine aminotransferase by 35.7 % (P<0.01), compared to the experimental group of vagotonic animals. In the experimental group with sympa-thotonia, the activity of aspartate aminotransferase was 1.88 times higher (P<0.001), alanine aminotransferase 1.84 times higher (P<0.001), compared to the experimental group of animals. It was established that feeding cows with feed additives based on a mixture of nanoaquahelates contributed to a decrease in the activity of blood enzymes. The prospect of further research is to adjust the doses of the applied feed additive to increase the productivity of cows individually to each tone of the autonomic nervous system and to study the effectiveness of the nanopreparation taking into account these parameters.